2014
DOI: 10.3126/kumj.v11i1.11055
|View full text |Cite
|
Sign up to set email alerts
|

Is Central Nervous System an Immune-Privileged Site?

Abstract: The central nervous system (CNS) was once considered to be an immune-privileged area. However, increasing evidence shows that the central nervous system is not an immune-privileged but is an active surveillance site. There is a bi-directional communication between the central nervous system and immune system. Normally, immune cells migrate into the central nervous system microenvironment through choroid plexus and interact with the central nervous system resident cells through either through neuromediators or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 91 publications
0
8
0
1
Order By: Relevance
“…136,138 The classical view that regarded the CNS as an immune-privileged site by virtue of the imperm eable blood-brain barrier has evolved to a view of significant interactions between the CNS and immune system. 139 Through such processes, cells of the nervous system such as microglia, astrocytes, oligodendrocytes, Schwann cells in the peripheral nervous system, endothelial cells of the brain microvasculature, and even neurons can release cytokines and chemokines (Figure 3). 139 Finally, notable changes in neurotransmitter levels have been detected in male Wistar rat models of AKI, including decreased dopamine turnover in the striatum, mesencephalon, and hypothalamus, which can substantially effect learning, memory, anxiety, and depression.…”
Section: Cognitive Impairment In Uraemiamentioning
confidence: 99%
“…136,138 The classical view that regarded the CNS as an immune-privileged site by virtue of the imperm eable blood-brain barrier has evolved to a view of significant interactions between the CNS and immune system. 139 Through such processes, cells of the nervous system such as microglia, astrocytes, oligodendrocytes, Schwann cells in the peripheral nervous system, endothelial cells of the brain microvasculature, and even neurons can release cytokines and chemokines (Figure 3). 139 Finally, notable changes in neurotransmitter levels have been detected in male Wistar rat models of AKI, including decreased dopamine turnover in the striatum, mesencephalon, and hypothalamus, which can substantially effect learning, memory, anxiety, and depression.…”
Section: Cognitive Impairment In Uraemiamentioning
confidence: 99%
“…Consequently, one might conclude that the signaling effects of rituximab on B cells may contribute to the anti-tumor activity of rituximab in a manner that is not relevant to immune participation. Although, we must be cautious since more recent observations have suggested that the central nervous system is not an immune-privileged but rather it could be considered as an active surveillance site where activated immune cells can cross the blood-brain barrier (Shrestha et al, 2013).…”
Section: Chemosensitizationmentioning
confidence: 99%
“…The brain has been considered to be an “immune-privileged” organ, isolated from the peripheral immune system (Shrestha et al, 2013). However, recent evidence shows that there is bi-directional communication between the brain and the peripheral immune system (Holmes and Butchart, 2011).…”
Section: Systemic Inflammation and Admentioning
confidence: 99%